2014
DOI: 10.1159/000356063
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary Detrusor Contraction Is a Frequent Finding in Patients with Recurrent Urinary Tract Infections

Abstract: Objective: To check whether subtle voiding dysfunction is related to recurrent urinary tract infection (rUTI). Methods: 254 consecutive patients with at least four episodes of urinary tract infection (UTI) were studied. At least three repeat urodynamic evaluations with an additional ice water test to maximize the detection of involuntary detrusor contraction (IDC) were used. Stress urinary incontinence cases were used as controls. Nonparametric univariate and multivariate analyses were used for statistics. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…As we have previously highlighted, this suggests possible relevance of central sensitization even to ostensibly nonpainful conditions, such as OAB . At present, we can only speculate as to any source of persistent C‐fiber input that might first initiate central sensitization in OAB, but investigators have suggested roles for urinary tract infection, urinary retention, and other precipitating events, which could represent the requisite high‐threshold stimulation for the “silent” bladder C‐fiber activation needed for central sensitization induction …”
Section: Discussionmentioning
confidence: 79%
“…As we have previously highlighted, this suggests possible relevance of central sensitization even to ostensibly nonpainful conditions, such as OAB . At present, we can only speculate as to any source of persistent C‐fiber input that might first initiate central sensitization in OAB, but investigators have suggested roles for urinary tract infection, urinary retention, and other precipitating events, which could represent the requisite high‐threshold stimulation for the “silent” bladder C‐fiber activation needed for central sensitization induction …”
Section: Discussionmentioning
confidence: 79%
“…The characteristics of excluded studies: 11 studies were excluded after the review of the full manuscript. Data was not extractable in 2 studies [20,21]. One study was focusing at the incidence of recurrent UTIs and did not report on investigation findings [2].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…In normal physiological conditions, bladder distention activates the non-nociceptive A␦ afferents that trigger a spinobulbospinal reflex (10), while nociceptive C-fiber afferents are silent (14). In pathological conditions such as spinal cord injury (7,9) or bladder infection/irritation that induce bladder overactivity (21), the nociceptive C-fiber afferents are also activated which triggers a spinal micturition reflex (14,27).…”
mentioning
confidence: 99%